Knockdown of zinc finger protein 267 suppresses diffuse large B-cell lymphoma progression, metastasis, and cancer stem cell properties. Issue 1 (1st January 2022) - Yang, Hua; Wang, Linmei; Zheng, Yingbin; Hu, Guiming; Ma, Hongyan; Shen, Liyun
ABSTRACT: Zinc finger protein 267 (ZNF267) is a member of the Kruppel-like transcription factor family, which regulates various biological processes such as cell proliferation and differentiation. However, the biological significance of ZNF267 and its potential role in diffuse large B-cell lymphoma (DLBCL) remain to be documented. Experiments were herein conducted to study the role of ZNF267 in DLBCL. real-time quantitative reverse transcription PCR and Western blotting assays were conducted to detect the expression of ZNF267 in tissues and cells. Tissue microarray and bioinformatics analyses of public data were also done to detect the expression status and clinical significance of ZNF267. Functional cell experiments including CCK8 assay, colony formation assay, 5-ethynyl-2ʹ-deoxyuridine (EDU) assay, terminal deoxynucleotidyl transferase biotin-dUTP nick end labeling (TUNEL) assay, transwell assay, and wound healing assay were conducted to study the effects of ZNF267 knockdown and overexpression on cell proliferation and mobility. Xenograft assay was also conducted to confirm the effects of ZNF267 knockdown in vivo . In the present study, we found ZNF267 was significantly upregulated in DLBCL and predicted a poor survival outcome based on the bioinformatics analysis. Functionally, the knockdown of ZNF267 resulted in less cell proliferation and mobility, whereas the overexpression led to enhanced cell proliferation and mobility. Animal experiments also confirmed that ZNF267 silence contributed to less tumor growth and less lung metastasis. Further analysis showed that ZFN267 knockdown resulted in decreased epithelial-mesenchymal transition (EMT) and cancer stem cell (CSC) properties. Our results suggest that ZNF267 is an oncogene in DLBCL and its silence could compromise the aggression of DLBCL, which makes ZNF267 a promising therapeutic target.